Fighting for Olympic dreams and life beyond: Olympian judokas on striving for glory and tackling post-athletic challenges - Hong, Hee Jung; Hong, Seung Han (Frontiers in Psychology, 2023)
Objectives: This study explores the experiences of Olympian judokas, examining both their pursuit of excellence to compete at the Olympics and their subsequent transition out of judo. The aim is to offer empirical evidence regarding the challenges they face in realizing their Olympic dreams, and to shed light on the transitional challenges, available resources, and needs they face as they move towards post-athletic lives. Methods: We conducted semi-structured interviews with eight Olympian judokas: five males and three females, all of whom have retired from competitive judo. These participants are from Portugal (n = 1), South Korea (n = 2), and the U.K. (n = 5). We employed thematic analysis, which led to the identification of five main themes: (a) From Dreams to Olympic Reality, (b) Facing the Void: Loss of Goals and Identity, (c) The Crucial Role of Social Support, (d) Dual Aspects of Pre-Retirement Planning, and (e) The Double Edge of Organizational Support. Findings: The findings highlight the significant challenges faced by Olympian judokas, including goal and identity loss post-retirement, and the need for comprehensive and accessible organizational support, particularly psychological assistance, to assist in their transition to post-athletic life Implications: The findings not only enhance our understanding of judokas’ experiences during transition but also offer insights that could guide the development of tailored support programs. It is critical for sport governing bodies and practitioners to apply these insights in creating comprehensive and easily accessible support systems, which will ensure a smoother transition to post-athletic life for high-performance athletes.